Effect of Irradiation and Temperature on Microstructural Characteristic of FeCrAl Alloys - Voiculescu, Ionelia; Geanta, Victor; Stanciu, Elena Manuela; Jianu, D.A.; Postolache, C.; Fugaru, Viorel (Institute of Physics, Polish Academy of Sciences, 2018)
Characteristics of FeCrAl alloys family are currently investigated in order to determine their behavior in different types of environment, erosive and corrosive (solid, liquid or gaseous), at high temperatures (400–1000 ◦C). The application with a special impact of these alloys consists in their use to build structural components of nuclear power plant (IV generation) at which the cooling medium is made of liquid metal with very high heat transfer capacity (Pb, Pb-Bi, Sn etc). To improve the resistance in extreme conditions (corrosion, erosion, high temperature) of the alloy, a superficial oxide layer may be formed, which constitutes an effective barrier against the destructive action of the working environment. This paper presents some results obtained regarding the influence of gamma irradiation on a FeCrAl alloy surface, after the sample surface was superficially remelted by laser and maintained in molten lead in furnace at 500 ◦C for 6 to 12 months. Metallographic aspects, such as microstructural changes, layer thicknesses and homogeneity are analyzed. New compounds formed after irradiation using Co-60 gamma rays are investigated